EPISCOPUL VALERIAN ZAHARIA: ÎNTRE SFÂNTUL SINOD ȘI PUTEREA COMUNISTĂ - GEORGE EUGEN ENACHE (Analele Universităţii "Dunărea de Jos" din Galaţi. Fascicula XIX, Istorie)
Valerian Zaharia was bishop of Oradea from 1951 to 1969. Little has been written about his life and work. This is motivated by his controversial past, characterized by close collaboration with the communist regime. This collaboration is attested by many writings of the bishop but also by many files of the former Securitate. From these documents it emerges who Bishop Valerian Zaharia really was, and the purpose of this article is to outline this biography that remained secret for a long time.